Rapidly Progressive Malignant Fibrous Histiocytoma of Right Atrium: a Rare Case Report - Aksu,Timucin (2019)
Abstract We are going to present a case of malignant fibrous histiocytoma in the right atrium, which is a very rare entity. The patient had a right atrial mass, which prolapsed through the tricuspid valve into the right ventricle, causing functional tricuspid valve stenosis. The tumor was completely resected and the patient had an uneventful postoperative period. Histopathological examination reported malignant fibrous histiocytoma. The patient presented to the emergency department five weeks after discharge with dyspnea and palpitation. Echocardiography and magnetic resonance imaging revealed recurrent right atrial tumor mass. His clinical status has worsened, with syncope and acute renal failure. On the repeated echocardiography, suspected tumor recurrence was observed in left atrium, which probably caused systemic embolization. Considering the aggressive nature of the tumor and systemic involvement, our Heart Council decided to provide palliative treatment by nonsurgical management. His status deteriorated for the next few days and the patient succumbed to a cardiac arrest on the 4th day.